Characterization and Hydrocarbon Identification of Liquid Fuel from Mixed Waste Plastics at Different Heating Time Intervals - Kigozi, Moses; Wasswa, John; Ntale, Muhammad; Nkedi-Kizza, Peter (International Journal of Scientific & Engineering Research, 2016)
Mixed waste plastics which included High Density Polyethylene ((HDPE), Low Density Polyethyline (LDPE),Polystyrene (PS), Polypropylene (PP), Polyethylene Terephthalate (PET) were investigated for production, characterization and hydrocarbon identification of fuel obtained from the plastics by catalytic pyrolysis. Silica-alumina was used as the catalyst. The mixed waste plastics were heatedfor one hour and two hours of contact time. The operation temperatures ranged between 250oC to 370oC giving a yellowish liquid after condensing the vapors with a chiller at 5oC. The reactor was connected to a fractionating column of one meter long and then to the condenser. The production ranged between 58 to 73% liquid, 18 to 34% cake and the rest was estimated as gas. The samples were investigated with different parameters based on diesel standards due to the wide range of hydrocarbon content. The parameters showed acceptable average ranges; cloud point 4oC, flash point 79.4 oC, kinematic viscosity 2.18 mm2/s, sulfated ash 4.7x10-5%, copper strip corrosion 1a, cetane number 63, acid number 72.9 μg and densities of 0.785 g/cm3. The identification of the hydrocarbons showed that the fuel falls into four classes of fuel which include diesel, aviation, naphtha and oil due to the range of hydrocarbons from C8 to C28 when analyzed with GC/MS and named from GC library
Keywords: Cloud point; Flash point; Kinematic viscosity; Sulfated ash; Acid number; Diesel; Aviation; Naphtha; Oil